On the zero locus of ideals defining the Nash blowup of toric surfaces. Issue 3 (4th March 2018) - Chávez Martínez, Enrique; Duarte, Daniel
ABSTRACT: We consider the problem of finding an ideal whose blowup defines the Nash blowup of a toric surface and such that its zero locus coincides with the singular set of the toric surface.